2017
DOI: 10.1002/zaac.201700259
|View full text |Cite
|
Sign up to set email alerts
|

The Crystal Structures of Pb5Sb4S11 (Boulangerite) – A Phase Transition Explains Seemingly Contradictory Structure Models

Abstract: Abstract. In the literature, many seemingly contradictory structure models of boulangerite, ideally Pb 5 Sb 4 S 11 , and the related mineral falkmanite have been reported. These can be explained by a phase transition between a low-temperature (LT) modification (P2 1 /c, a ≈ 8.07 Å, b ≈ 23.5 Å, c ≈ 21.6 Å, β ≈ 100.7°) and a disordered hightemperature (HT) modification [Pnma, a = 23.530(2) Å; b = 4.0385(8) Å and c = 21.273(2) Å, R 1 (obs) = 0.039] that occurs above ca. 350-400°C. The almost completely ordered di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 36 publications
0
1
0
Order By: Relevance
“…250 °C may indicate an alteration of the structure or the composition, for example, due to exsolution processes or an order−disorder transition as observed for Pb 5 Sb 4 S 11 . 71 Subsequent SEM and TEM studies on the sample revealed a decomposition of the sample into a Sn-enriched phase with L4,4-type structure (space group Pnma) and small amounts of a Bi-enriched unknown phase (see Figure S13 and Table S15 in the Supporting Information). The phase stability was not further investigated due to the poor thermoelectric properties.…”
Section: Resultsmentioning
confidence: 99%
“…250 °C may indicate an alteration of the structure or the composition, for example, due to exsolution processes or an order−disorder transition as observed for Pb 5 Sb 4 S 11 . 71 Subsequent SEM and TEM studies on the sample revealed a decomposition of the sample into a Sn-enriched phase with L4,4-type structure (space group Pnma) and small amounts of a Bi-enriched unknown phase (see Figure S13 and Table S15 in the Supporting Information). The phase stability was not further investigated due to the poor thermoelectric properties.…”
Section: Resultsmentioning
confidence: 99%